Pelatihan Pembuatan Sistem Peringatan Dini Bencana Gempabumi Menggunakan Bandul Bagi Masyarakat Kawasan Pesisir Kabupaten Cilacap - Muhammad Sehah (Universitas Jenderal Soedirman, 2021)
The Activities of Community Services (PKM) – The Application of Science and Technology program has been done with the entitle “Training on Manufacturing of Simple Equipment for Earthquake Early Warning Using a Pendulum for the Coastal Area Community of Cilacap Regency”. The purpose of this activity is to disseminate the introduction of an early warning system of earthquakes for rural communities in the coastal area of ​​Cilacap Regency and technical training for making simple equipment for earthquake early warning using a pendulum. The method used in this activity is the combination of discourse, discussion, and practice. After transfer of technology has been done, largely participant gives positive response for this community services activity, and there is a desire to implement and disseminate it. The average attainment index of this community services activity successfulness based on the observations results using a questionnaire is 82.03%; with highest index is 87.50% and lowest index is 73.75%. The participant understanding to the matters of transfer of technology and socialization given were enough optimal. It can be known on the recapitulation results of pre-test and post-test values, where the average pre-test value is 3.79 and the post-test is 6.95. Thus, there is the value ascension about 83.33%, and it shows that the mastery and understanding of the knowledge given has approached expectations